Secure distribution of heterogeneous multimedia content on the internet. (9th May 2006) - Noore, Afzel
This paper presents an architecture for a distributed conditional access system with multiple service providers. The standard XML digital signature and XML encryption techniques are applied to ensure secure distribution of audio, video, image and data on the web. The proposed approach seamlessly integrates the payment transactions with content delivery in a secure environment.